Kedudukan dan Fungsi Kaidah Tafsir dalam Penafsiran Al-Qur’an - Ahmad Faqihudin (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2021)
Al-Qur'an is very rich in meaning that still requires study to be able to know what and how the essence of its content. The ideal reading of the Al-Qur'an requires the rules that needed to be followed so the results of the reading of the Al-Qur'an are in accordance with what is expected. This study aims to examine three main principles in the process of interpreting Al-Qur'an. These are the rules of ushul fiqih, the rules of language, and the rules of logic. By the literature study method used, at the end of this study the researcher concludes that the rules are needed as an effort to minimize mistakes in studying Al-Quran, so as not to cause fatal mistakes for someone in studying the verses of the Qur'an.